Digital Transformation in English Material Development: Opportunities and Challenges for EFL Curriculum Designers - Nabilah Dafa Rusliani; Siti Alifa Nurhaliza; Fatir Ahmad Fachrezy; Selnistia Hidayani (PT. Intelek Cendikiawan Nusantara, 2025)
Digital transformation has significantly changed the development of English teaching materials, especially in the context of English as a Foreign Language (EFL). These changes require curriculum designers to adjust their strategies and approaches so that teaching materials remain relevant, effective, and in line with the demands of 21st-century learning. This article focuses on analyzing the opportunities and challenges arising from the development of digital-based teaching materials by examining key concepts and frameworks in curriculum and teaching material development. This study uses a literature review approach, referring to theoretical sources related to curriculum design, types of digital materials, and principles of material evaluation. The findings show that digital transformation offers significant opportunities, including wider access to learning resources, flexible learning environments, and enhanced interactivity. However, challenges such as limited digital literacy, infrastructure constraints, and the need for rigorous material quality evaluation require careful attention. Overall, this study concludes that digital transformation has the potential to improve the quality of EFL material development, provided that curriculum designers have adequate digital competence and apply appropriate material evaluation principles